137 High Flow Nasal Cannulae (HFNC) or Nasal Continuous Positive Airway Pressure (NCPAP) Post-Extubation in Premature Infants? a Randomised Controlled Trial. (October 2012) - Collins, C; Holberton, JR; Barfield, C; Davis, PG
Abstract : Background: NCPAP facilitates successful extubation. It is unclear whether HFNC are as effective as NCPAP in preventing extubation failure. In addition to an alternative modality of respiratory support HFNC may result in less nasal trauma than NCPAP. Methods: 132 preterm ventilated infants were randomised and stratified by gestation(< 28 vs 28–32 weeks). Primary outcome was extubation failure defined by a composite of 3 pre-specified failure criteria in the 7 days post-extubation. Individual failure criteria were not mutually exclusive and are defined; Apnoea, > 6 episodes in 6 hours or 1 requiring IPPV, Acidosis, pH< 7.25 & pCO2 >66mmHg, and >15% increase in FiO2 from extubation. A nasal trauma score was adapted from Kaufman [E-PAS 2007:61390]. Results: Conclusions: Rates of extubation failure were not significantly different between the groups. HFNC resulted in significantly less nasal trauma than NCPAP. This benefit may need to be considered in post-extubation respiratory support for preterm infants.